Locust Hemolymph Conveys Erythropoietin-Like Cytoprotection via Activation of the Cytokine Receptor CRLF3 - Knorr, Debbra Y.; Hartung, Denise; Schneider, Kristin; Hintz, Luzia; Pies, Hanna S.; Heinrich, Ralf (Frontiers in Physiology, 2021)
The cytokine receptor-like factor 3 (CRLF3) is an evolutionary conserved class 1 cytokine receptor present in all major eumetazoan groups. Endogenous CRLF3 ligands have not been identified and the physiological responses mediated by mammalian CRLF3 are poorly characterized. Insect CRLF3 is activated by erythropoietin (Epo) and several related molecules that protect mammalian neurons from stress-induced apoptosis. However, insects neither express Epo nor “classical” Epo receptor. Cell-protective effects of insect hemolymph have been described for several species. In this study, we explored the possibility that the endogenous CRLF3 ligand is contained in locust hemolymph. PCR analyses confirmed expression of crfl3-transcripts in neurons and hemocytes of Locusta migratoria and Tribolium castaneum. Survival of locust hemocytes in primary cultures was significantly increased by supplementation of culture medium with locust hemolymph serum. Locust primary neuron cultures were also protected by locust hemolymph, though preceding exposure to fetal bovine serum changed the hemolymph dose-dependency of neuroprotection. Direct comparison of 10% hemolymph serum with recombinant human Epo in its optimal neuroprotective concentration revealed equivalent anti-apoptotic effects on hypoxia-exposed locust neurons. The same concentration of locust hemolymph serum also protected hypoxia-exposed T. castaneum neurons. This indicates that the neuroprotective factor in locust hemolymph is sufficiently conserved in insects to allow activation of neuroprotective receptors in different species. Locust hemolymph-induced neuroprotection in both L. migratoria and T. castaneum was abolished after RNAi-mediated suppression of crlf3-expression. In summary we report the presence of a conserved endogenous cytokine in locust hemolymph that activates CRLF3 and connected anti-apoptotic processes in hemocytes and neurons. Identification and characterization of the CRLF3 ligand will promote knowledge about cytokine evolution and may unravel cell-protective agents with potential clinical application.